2014
DOI: 10.1155/2014/472949
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Illness in Prostate Cancer Patients with a Low-to-Moderate Risk of Progression: A One-Year, Pan-European Observational Study

Abstract: Objective. To assess the impact of low-to-moderate risk prostate cancer on patients' quality of life (QoL) at diagnosis and within the first year of treatment. Subjects and Methods. Men (n = 672) aged 50–75 years with prostate cancer (Gleason score ≤7, PSA ≤20 ng/mL and clinical staging T1c–T2b) were enrolled in five European countries. Patients completed five questionnaires, including EORTC Quality of Life Questionnaire—Prostate Cancer 25 (QLQ-PR25) and EORTC Quality of Life Questionnaire—Cancer 30 (QLQ-C30).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 22 publications
3
19
0
1
Order By: Relevance
“…The negative impact of prostate cancer and treatment‐related symptoms as urinary symptoms, bowel symptoms and sexual dysfunction on HRQoL is well described . In our study, we found a significant but weak correlation between global health and sexual activity, sexual functioning, urinary symptoms and incontinence ( r = −0.22, P < 0.002), confirming the earlier described findings.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The negative impact of prostate cancer and treatment‐related symptoms as urinary symptoms, bowel symptoms and sexual dysfunction on HRQoL is well described . In our study, we found a significant but weak correlation between global health and sexual activity, sexual functioning, urinary symptoms and incontinence ( r = −0.22, P < 0.002), confirming the earlier described findings.…”
Section: Discussionsupporting
confidence: 91%
“…For urinary symptoms and sexual function scales internal consistency is good (α = 0.70-0.86) [21]. The use of these questionnaires to assess the HRQoL in prostate cancer patients is internationally validated and well accepted in Europe as well in the Netherlands [22][23][24][25]. Internal consistency based on the current data was good for EORTC QLQ-C30 (α = 0.65-0.92).…”
Section: Health-related Quality Of Lifementioning
confidence: 94%
“…The increase in AS patients' generalized anxiety symptoms over time contradicts previous research that reported declining anxiety in this group . Much of international AS research has been conducted on men being managed in centers with a strong focus on AS who have been refining and perfecting the diagnosis experience for almost two decades, and therefore AS is more widely accepted by clinicians and patients .…”
Section: Discussionmentioning
confidence: 68%
“…This could suggest that the intervention is acting as a support, diminishing some of the overall impact of treatment and side effects on HRQoL. There is also evidence building across the literature, which suggests the EQ-5D instrument may not be sensitive enough to pick up changes in HRQoL for men with prostate cancer given the average age range of diagnosis (26,27). Hence the EQ-5D VAS scores may be more applicable to this analysis, which, when utilised, highlighted cost effectiveness.…”
Section: Discussionmentioning
confidence: 99%